5 - Commodifying the Female Body: Xenophobic Violence in South Africa - Nkealah, Naomi (Africa Development, 2021)
The competition for scarce resources within a multi-ethnic community often results in conflicts between ‘indigenous’ peoples and ‘foreign’ migrants, or, to use Francis Nyamnjoh’s expression, between ‘insiders and outsiders’ (Nyamnjoh 2006). Such conflicts are manifested in vari- ous ways, ranging from verbal abuse to physical assault. This expres- sion of hostility, in both word and deed, towards immigrants is what has been termed xenophobia. In May 2008, xenophobic violence against African immigrants broke out in the South African township of Alexandra, and thereafter the violence spread to most parts of the country. Several reasons were put forward in the media in an attempt to explain the cause of the violence, inclusive of which was the claim that foreigners were taking ‘our jobs and our women’. Using this statement as a starting point, this article looks at ways in which conceptualisations of masculinities within a racialized South African public sphere are played out in the xenophobic attacks directed towards immigrants in Alexandra. It looks at cyberspace as a ‘public sphere’ and interrogates the gender implications of using this medium to frame xenophobic violence within the context of contesting masculinities.